Impact of periprocedural factors on revascularization success and good clinical outcomes in anterior circulation stroke patients treated with mechanical thrombectomy - Kurminas , M.; Berūkštis , A.; Misonis , N.; Tamošiūnas , A. E.; Jatužis , D. (Neurologijos seminarai, 2019)
Background. Constantly evolving guidelines for the treatment of ischemic stroke in light of widely published clinical trials show no final consensus; many factors that may significantly alter treatment outcomes are still under investigation. Each stroke center treats patients with ischemic stroke due to major artery occlusion differently depending on available resources, expert judgment, and clinical experience. The aim of this study was to evaluate the influence of periprocedural factors (intravenous thrombolysis, balloon-occlusive catheter use, number and timing of thrombectomy sessions, and type of anesthesia) on recanalization success and good clinical outcomes.Materials and methods. We included 191 patients who were treated with mechanical thrombectomy (MTE) due to large vessel occlusion in the anterior circulation from January 2015 to November 2018 in Vilnius University Hospital Santaros Clinics. Demographic, work organization, and clinical variables were evaluated. The primary outcome was functional independence after 90 days (modified Rankin scale 0-2). Secondary outcomes were successful reperfusion (TICI 2b-3) and change in neurological status by NIHSS at 2 and 24 hours.Results. No significant difference in outcomes was found between MTE groups of direct and combined therapy, the balloon-occlusive catheter use or the type of applied anesthesia. MTE procedure time is related to the recanalization success and good clinical outcome (p
Keywords: ischemic stroke; mechanical thrombectomy; thrombolysis; clinical outcome; periprocedural factors